GOLD IMMUNOCHROMATOGRAPHIC ASSAY (GICA) SEBAGAI IMUNOSENSOR MENDETEKSI ANTIBODI Bacillus Anthracis PENYEBAB PENYAKIT ZOONOSIS - Gunarti Gunarti; Yunan Jiwintarum; Awan Dramawan; Lale Budi Kusuma Dewi (Jurnal Kesehatan Prima, 2015)
Abstract: The purpose of this study was to identify patterns of protein antigens full / secretory antigens may be antigenic protein (PA) of Bacillus anthracis by the use of SDS-PAGE method (Laemmli) which can be used as bioreseptor on the test device fabrication method for detecting antibodies GICA of Bacillus anthracis , identify patterns of proteins that are antigenic protein (PA) or indicate the nature of the reactivity of Bacillus anthracis by using Western blotting and Determining the specificity and sensitivity of the test method to detect antibodies GICA Bacillus anthracis when using the results of the ELISA method as a reference. This study is a descriptive observational study. Research variable antigenic protein of Bacillus anthracis as bioreseptor and Antibodies from Bacillus anthracis as imunosenssor. The test prototype test device made using 20 sample with ELISA as a reference for calculating the sensitivity and specificity. The results of this study were identified band – band of 92 kDa, 68 kDa, 54 kDa, 43 kDa, 29 kDa and 18 kDa that can be used as bioreseptor on GICA, identified a pattern of proteins that are antigenic or indicate the nature of the reactivity of the Bacillus anthracis 68 kDa by Western blotting using the method, extract secretory antigen (SA) Bacillus anthracis can be used as a test device bioreseptor on GICA method for the detection of IgG antibodies against Bacillus anthracis and sensitivity and specificity of the test method to detect antibodies GICA Bacillus anthracis when using the results of the ELISA method as a reference each is 100% and 87.5%.